EFFECT OF SIMPLIFIED KUNDALINI YOGA COMBINED WITH ACUPRESSURE ON ETHYL GLUCURONIDE (ETG) LEVELS AND LIFE SATISFACTION AMONG ALCOHOLIC MIDDLE-AGED MEN (CAHIERS MAGELLANES-NS, 2024)
Background: Alcoholism is a significant public health issue, particularly among middle-aged men, leading to adverse physical and mental health outcomes. Ethyl glucuronide (ETG), a reliable biomarker for recent alcohol consumption, provides a crucial measure of abstinence. Simplified Kundalini Yoga (SKY) and acupressure have been explored as complementary interventions for managing addiction and enhancing psychological well-being.Objective: This study aimed to investigate the efficacy of SKY combined with acupressure in reducing ETG levels and improving life satisfaction among middle-aged men with alcohol use disorder.Methodology: A total of 60 alcoholic men aged 40-60 years were randomly assigned to three groups: Group A (SKY + Acupressure), Group B (SKY only), and Group C (Control). The intervention lasted 12 weeks, with participants practicing SKY and/or receiving acupressure for 60 minutes daily. Pre- and post-intervention ETG levels were measured using urine samples, and life satisfaction was assessed via the Satisfaction with Life Scale (SWLS). Data were analyzed using paired t-tests and ANOVA.Results: Group A (SKY + Acupressure) showed the most significant reduction in ETG levels (p < 0.01) and improvement in life satisfaction (p < 0.01) compared to Group B (SKY only) and Group C (Control). ANOVA revealed significant differences between the groups in both ETG reduction and life satisfaction improvement.Conclusion: Simplified Kundalini Yoga combined with acupressure demonstrated significant benefits in reducing alcohol consumption and enhancing life satisfaction in middle-aged alcoholic men. These findings suggest the potential of integrative mind-body interventions in addiction recovery programs.